Fbxw7 controls angiogenesis by regulating endothelial notch activity - Izumi, Nanae; Helker, Christian; Ehling, Manuel; Behrens, Axel; Herzog, Wiebke; Adams, Ralf H. (PLoS ONE, 2012)
Notch signaling controls fundamental aspects of angiogenic blood vessel growth including the selection of sprouting tip cells, endothelial proliferation and arterial differentiation. The E3 ubiquitin ligase Fbxw7 is part of the SCF protein complex responsible for the polyubiquitination and thereby proteasomal degradation of substrates such as Notch, c-Myc and c-Jun. Here, we show that Fbxw7 is a critical regulator of angiogenesis in the mouse retina and the zebrafish embryonic trunk, which we attribute to its role in the degradation of active Notch. Growth of retinal blood vessel was impaired and the Notch ligand Dll4, which is also a Notch target, upregulated in inducible and endothelial cell-specific Fbxw7iECKO mutant mice. The stability of the cleaved and active Notch intracellular domain was increased after siRNA knockdown of the E3 ligase in cultured human endothelial cells. Injection of fbxw7 morpholinos interfered with the sprouting of zebrafish intersegmental vessels (ISVs). Arguing strongly that Notch and not other Fbxw7 substrates are primarily responsible for these phenotypes, the genetic inactivation of Notch pathway components reversed the impaired ISV growth in the zebrafish embryo as well as sprouting and proliferation in the mouse retina. Our findings establish that Fbxw7 is a potent positive regulator of angiogenesis that limits the activity of Notch in the endothelium of the growing vasculature. © 2012 Izumi et al.
CRIS-Team Scopus Importer:2020-09-23